Discovery of fluorobenzimidazole HCV NS5A inhibitors. Issue 22 (15th November 2016) - Randolph, John T.; Flentge, Charles A.; Donner, Pamela; Rockway, Todd W.; Patel, Sachin V.; Nelson, Lissa; Hutchinson, Douglas K.; Mondal, Rubina; Mistry, Neeta; Reisch, Thomas; Dekhtyar, Tatyana; Krishnan, Preethi; et al.
Graphical abstract: Abstract: Research toward a next-generation HCV NS5A inhibitor has identified fluorobenzimidazole analogs that demonstrate potent, broad-genotype in vitro activity against HCV genotypes 1–6 replicons as well as HCV NS5A variants that are orders of magnitude less susceptible to inhibition by first-generation NS5A inhibitors in comparison to wild-type replicons. The fluorobenzimidazole inhibitors have improved pharmacokinetic properties in comparison to non-fluorinated benzimidazole analogs. Discovery of these inhibitors was facilitated by exploring SAR in a structurally simplified inhibitor series.